Implementation of Node Harvester Technology For Sustainable Telecomunication Network Provision in Rural Areas. (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This research examines the application of Node Harvester technology as a solution to provide sustainable telecommunications networks in rural areas. Given the limited telecommunications infrastructure in remote areas, Node Harvester offers an innovative approach by utilizing renewable energy sources, such as solar and wind power. This research examines the effectiveness of this technology implementation in improving the accessibility and quality of telecommunications services. The methods used include field analysis, user surveys, and system performance evaluation. The results indicate that Node Harvester implementation can improve telecommunications networks by up to 70% in rural areas. Furthermore, this implementation also contributes to reduced operational costs and increased environmental sustainability. These findings have important implications for the development of telecommunications infrastructure in rural areas and encourage the use of environmentally friendly technologies. This research is expected to serve as a reference for relevant parties in designing and implementing more efficient and sustainable telecommunications solutions in rural areas.